MOTIF KHALAYAK RW 007 GUNUNG GEDANGAN, MOJOKERTO MELIHAT TAYANGAN MAHABARATA - Novika, Iga; Handoko, Rudy; Rochim, Achludhin Ibnu (Universitas 17 Agustus 1945 Surabaya, 2015)
Television is one of the mass media which serves to provide information and entertainment to thepublic at large. In the development of a lot of programs that have been given by the mass media oftelevision as a public spectacle. Increasing number of events presented by television stations making thecommunity to choose a program that will show they consume. Institutions not only television stationserving domestic production alone event in obtaining public interest, but several television programs buymovie production abroad to be used as reference in the attention of audiences. One television stationprograms favored by our society today is a drama series Mahabharata. colossal drama series producedby the Indian state is able to attract the attention of television viewers. Formulation of the problem in thisresearch is